1990
DOI: 10.21273/jashs.115.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Apple Thinning by Photosynthetic Inhibition

Abstract: Shading (92%) of `Redchief Delicious' apple (Malus domestics Borkh.) trees for 10-day periods from 10 to 20, 15 to 25, 20 to 30, and 25 to 35 days after full bloom (DAFB) caused greater fruit abscission than shading from 5 to 15, 30 to 40, 35 to 45, or 47 to 57 DAFB. Fruit 8 to 33 mm in diameter (10 to 30 DAFB) were very sensitive to 10 days of shade, even though fruit sizes of 6 to 12 mm are considered the most sensitive to chemical thinners. In a second test, shading for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 6 publications
5
46
0
Order By: Relevance
“…Application of thinners to such fruitlets may result in excessive thinning and reduced rates are often recommended (Williams, 1979). Byers et al (1990aByers et al ( , 1990bByers et al ( , 1991 have extensively tested the effect of shading and application of photosynthesis-inhibiting chemicals in early fruit growth, to assess the role of suppressed photosynthesis on degree of fruit thinning both with and without application of chemical thinners. They propose (Byers et al, 1990b) that cloudy periods for as little as 3 d or fewer during the physiological drop period may signifi cantly decrease fruit retention and may infl uence response to chemical thinners.…”
Section: Ditions On Mechanism Of Actionmentioning
confidence: 99%
“…Application of thinners to such fruitlets may result in excessive thinning and reduced rates are often recommended (Williams, 1979). Byers et al (1990aByers et al ( , 1990bByers et al ( , 1991 have extensively tested the effect of shading and application of photosynthesis-inhibiting chemicals in early fruit growth, to assess the role of suppressed photosynthesis on degree of fruit thinning both with and without application of chemical thinners. They propose (Byers et al, 1990b) that cloudy periods for as little as 3 d or fewer during the physiological drop period may signifi cantly decrease fruit retention and may infl uence response to chemical thinners.…”
Section: Ditions On Mechanism Of Actionmentioning
confidence: 99%
“…To avoid the confounding effect of shading treatment on fruit drop (Byers et al, 1990), or treatment effects on cell division, all treatments were delayed until 60 d after full bloom (DAFB). The trial also aimed to examine changes in the DM composition of fruit as influenced by these treatments and to examine the use of apoplastic fluid as an indicator of the carbohydrate supply to fruit.…”
mentioning
confidence: 99%
“…Young spur apple leaves play a vital role in supplying the developing fruits with carbohydrates (Corelli Grappadelli, 2003) and in fruit retention (Ferree and Palmer, 1982). A reduction in Pn after application of caustic materials at bloom (McArtney et al, 2006;Noordijk and Schupp, 2003) or from shading or Pn inhibitors (Byers et al, 1990a(Byers et al, , 1990b has been suggested as a causal factor in fruit thinning (Byers, 2003). Injury to spur leaves or shading followed by reductions in Pn could reduce fruit size.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to spur leaves or shading followed by reductions in Pn could reduce fruit size. However, support for this theory from thinning trials is inconsistent (Byers et al, 1990a(Byers et al, , 1990bFallahi, 1997;Fallahi et al, 1997;Noordijk and Schupp, 2003). In the present study, apple treated with Matran (Table 4) or eugenol (Tables 5 and 6) at sufficient rates to cause phytotoxicity showed no negative effects on fruit size.…”
Section: Discussionmentioning
confidence: 99%